The Validity and Practicality of SSCS-Based Student Worksheet on Ecology Material and Environmental Change - Syamsurizal; Irdawati; Violita; Refni Syahleli Afni; Muhamad Sholichin (Postgraduate, University of Mataram, 2023)
This research aims to produce student worksheet based on SSCS (Search, Solve, Create and Share). This type of research is development research using the Plomp model. The development stage of this model starts from the initial investigation stage, the development or prototyping stage, and the assessment stage. The instruments used in this development research were teacher questionnaire sheets, student response questionnaire sheets, self-evaluation sheets, and SSCS-based LKPD validation sheets (Search, Solve, Create and Share) by experts, as well as SSCS-based LKPD practicality assessment sheets (Search, Solve, Create and Share) which is filled in by teachers and students. The results showed that the SSCS-based LKPD (Search, Solve, Create and Share) was very valid with a score of 86.31%. The practicality assessment of student assessment in field trials (group evaluation) with a score of 92.00% with very practical criteria, and the practicality assessment by the teacher obtained a score of 96.00% with very practical criteria. It can be concluded that the LKPD based on SSCS (Search, Solve, Create and Share) that has been developed is included in the category of very valid and very practical.